Preschool Teachers’ Conceptions of Professional Development in Relation to Career Motivation and Job Satisfaction - Žveglič Mihelič, Mojca; Valenčič Zuljan, Milena; Plešec Gasparič, Romina (Revija za elementarno izobraževanje, 2025)
In this paper, we are interested in preschool teachers’ conceptions of professional development in relation to their motives for choosing the profession and professional satisfaction. Results of a study among 145 Slovenian preschool teachers show that they generally have a positive conception of professional development; nevertheless, recognition of the importance of learning and in-depth reflection on this conception depend on career motivations, while a broader conception of professional development increases the likelihood of thinking about leaving the profession more frequently. The findings justify the need for better recognition of preschool teachers’ needs and obstacles in the workplace.